2014
DOI: 10.1007/s10286-014-0255-9
|View full text |Cite
|
Sign up to set email alerts
|

Time sequence of autonomic changes induced by daily slow-breathing sessions

Abstract: Repeated daily session of music-guided SB increased parasympathetic modulation and decreased renal resistive index early in the study. These changes were being followed by a positive modulation of BRS and blood pressure reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Modesti et al . () reported that daily session of slow‐breathing increased parasympathetic modulation. Regular exercise improves HRV and parasympathetic activity, and reduces sympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Modesti et al . () reported that daily session of slow‐breathing increased parasympathetic modulation. Regular exercise improves HRV and parasympathetic activity, and reduces sympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Under physiological conditions RRI assay could detect phasic increase in renal vascular resistance induced by sympathetic activation obtained by cold pressor test or handgrip; in the same subjects the increase of blood volume by acute hydration resulted in an RRI decrease [27]. Repeated daily sessions of music-guided slow-breathing increased parasympathetic modulation and decreased RRI early in the study .These changes were being followed by a positive modulation of baroflex sensitivity and decrease in blood pressure [50]. In patients with heart failure high RRI values were associated with increased intrarenal vascular resistance due to neurohormonal hyperactivity and independently predicted heart failure progression [51].…”
Section: Role Of Arterial Vascular Resistancementioning
confidence: 95%
“…Controlled clinical trials in patients with hypertension have shown reductions in resting blood pressure and heart rate by long-term practice of SDB (Zou et al, 2017). Improvement in baroreflex sensitivity, increased parasympathetic modulation, and decreased sympathetic tone are proposed as possible underlying mechanisms (Cernes & Zimlichman, 2015;Modesti, Ferrari, Bazzini, & Boddi, 2015). In a recent clinical trial, hypertensive patients practiced controlled breathing at 0.1 Hz with or without inspiratory load of 20 cmH 2 O for 8 weeks.…”
Section: Clinical Applications Of Slow Deep Breathing With Inspiramentioning
confidence: 99%